Uptake and Immunomodulatory Properties of Betanin, Vulgaxanthin I and Indicaxanthin towards Caco-2 Intestinal Cells - Yunqing Wang; Ganwarige Sumali N. Fernando; Natalia N. Sergeeva; Nikolaos Vagkidis; Victor Chechik; Thuy Do; Lisa J. Marshall; Christine Boesch (MDPI AG, 2022)
The present study aimed to compare the absorption and transport patterns of three main betalains, betanin, vulgaxanthin I and indicaxanthin, into intestinal epithelial cells and to assess their distinct molecular effects on inflammatory and redox-related cell signalling in association with their radial scavenging potencies. All three betalains showed anti-inflammatory effects (5-80 μM), reflected by attenuated transcription of pro-inflammatory mediators such as cyclooxygenase-2 and inducible NO-synthase. Concomitant increases in antioxidant enzymes such as heme oxygenase-1 were only observed for betanin. Moreover, betanin uniquely demonstrated a potent dose-dependent radical scavenging activity in EPR and cell-based assays. Results also indicated overall low permeability for the three betalains with Papp of 4.2-8.9 × 10−7 cm s−1. Higher absorption intensities of vulgaxanthin and indicaxanthin may be attributed to smaller molecular sizes and greater lipophilicity. In conclusion, betanin, vulgaxanthin I and indicaxanthin have differentially contributed to lowering inflammatory markers and mitigating oxidative stress, implying the potential to ameliorate inflammatory intestinal disease. Compared with two betaxanthins, the greater efficacy of betanin in scavenging radical and promoting antioxidant response might, to some extent, compensate for its poorer absorption efficiency, as demonstrated by the Caco-2 cell model.